2018
DOI: 10.1371/journal.pone.0191568
|View full text |Cite
|
Sign up to set email alerts
|

Systematic identification of latent disease-gene associations from PubMed articles

Abstract: Recent scientific advances have accumulated a tremendous amount of biomedical knowledge providing novel insights into the relationship between molecular and cellular processes and diseases. Literature mining is one of the commonly used methods to retrieve and extract information from scientific publications for understanding these associations. However, due to large data volume and complicated associations with noises, the interpretability of such association data for semantic knowledge discovery is challengin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Results showed that the HPO-Orphanet+ is capable of providing a diagnostic graph mixed with both rare and common diseases, which has potential usage in rare disease differential diagnosis, especially for those rare diseases sharing similar symptoms with common diseases. In the future, we will upgrade the HPO-Orphanet+ by mining disease-gene information from literature [11, 63]. In addition, one recent research proposed a novel idea by introducing the concept of “property” as a third layer in addition to traditional two-layer disease-phenotype relationship [64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that the HPO-Orphanet+ is capable of providing a diagnostic graph mixed with both rare and common diseases, which has potential usage in rare disease differential diagnosis, especially for those rare diseases sharing similar symptoms with common diseases. In the future, we will upgrade the HPO-Orphanet+ by mining disease-gene information from literature [11, 63]. In addition, one recent research proposed a novel idea by introducing the concept of “property” as a third layer in addition to traditional two-layer disease-phenotype relationship [64].…”
Section: Discussionmentioning
confidence: 99%
“…Some other existing studies investigated the mining of associations between diseases and genes. For example, Zhang et al combined the Latent Dirichlet Allocation (LDA) [9] with network-based computational approach [10] to discover disease-gene associations from large amount of PubMed literature [11]. Piro et al developed a classification approach to predict disease-gene associations [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the future, we will combine graph network analysis approaches [58] [59] with clustering algorithm to provide network motif [60] analysis and LDA-based topic modelling [61]. Furthermore, parallel and distributed algorithms, using the indexing technique, will be developed.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of disease-associated genes can improve the understanding of disease etiology and development, thereby facilitating design and development of novel preventive and treatment strategies (7,8). Cross disease-gene studies and further pathway analyses provide an opportunity to resolve overlapping associations into discrete pathways and investigate possible shared etiologies (9,10).…”
Section: Introductionmentioning
confidence: 99%